Cultural Nativism in R.K. Narayan’s The Vendor of Sweets - Singh, Arun (The Outlook: Journal of English Studies, 2025)
Indian society has faced an inexorable crisis of the appropriation and rejection of the Western culture in the postcolonial phase. During the immediate decades in the wake of Independence, notions of nativism began to surface in the contemporary academic discourses and literary writings and challenged the cultural hegemony of the West. The Vendor of Sweets (1967) by R. K. Narayan is a thorough exercise in the concept of cultural nativism, which in its raw form constantly resists the cultural and capitalist hegemony of the West by virtue of its protagonist, Jagan. Jagan derives his ideas of nativism, though sometimes idiosyncratic, from the Hindu scriptures and his Gandhian philosophy. With these ideas, he poses a challenge to the manipulative hegemony, which his son Mali brings to his house after returning from America. The paper seeks to explore the idea of cultural nativism in Narayan’s novel and establish that in the name cultural plurality, the West harnesses and manipulates the indigenous cultures and maintains the power-structure through its capitalist ventures.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />